How do foreign language learning experiences influence the self-reference effect? - Xiaonan Dong; Jianshe Wu (Acta Psychologica)
People tend to display a processing bias towards information that is personally relevant, as opposed to information that is irrelevant to themselves. Such a bias can be influenced by long-term cultural experiences and temporary cultural priming tasks. However, the impact of the latter is transient, and it is unclear if an intermediate influence, more lasting than temporary priming tasks but less enduring than a cultural background, such as language learning, could induce a similar and stable processing bias. Given that language can shape people's mindset, this study aimed to investigate whether language learning experiences could affect participants' self-processing bias during a decision-making task. The findings showed that while behavioral results were not significant, ERP data indicated that advanced learners had more negative late N400 and P600 components for moderately self-relevant stimuli compared to highly self-relevant ones, mainly in the left or medial hemispheres. Beginners exhibited similar trends with marginal effects from fronto-central to parietal regions. Additionally, beginners displayed more negative N100 and early N400 responses and lacked a left-lateralized low-beta burst compared to advanced learners. These results suggest that the self-reference effect is present in both L2 beginners and advanced learners but is more pronounced in advanced learners. Notably, advanced learners with extensive English experience are more influenced by Western independent self-construal than beginners, leading them to focus more on highly self-related information and exhibit a stronger self-reference effect.